Complete Mesocolic Excision With Central Vascular Ligation in Comparison With Conventional Surgery for Patients With Colon Cancer – The Experiences at Two Centers - Mohamed Abdelkhalek; Ahmed Setit; Francesco Bianco; Andrea Belli; Adel Denewer; Tamer Fady Youssef; Armando Falato; Giovanni Maria Romano (Annals of Coloproctology, 2018)
Purpose Revolutions have occurred over the last 3 decades in the management of patients with colorectal cancer. Most advances were in rectal cancer surgery, especially after the introduction of the total mesorectal excision (TME) by Heald. However, no parallel advances regarding colon cancer surgeries have occurred. In 2009, Hohenberger introduced a new concept trying to translate the survival advantages of TME to patients with colon cancer. This relatively new concept of a complete mesocolic excision (CME) with central vascular ligation (CVL) in the management of patients with colon cancer represents an evolution in operative technique. We performed a comparative study between CME with CVL and conventional surgery for patients with colon cancer at Italian and Egyptian cancer centers, considering surgical quality and clinical outcome. Methods Seventy-nine Egyptian patients underwent conventional surgery (non-CME group) while 52 Italian patients underwent CME with sharp dissection between the embryological planes and CVL of the supplying vessels (CME group). Results Significantly better results were observed in terms of lymph node yield (CME group: 22.5 vs. non-CME group: 12; P < 0.0001) and lymph node ratio (CME group: 0.03 vs. non-CME group: 0.22; P < 0.0001). Regarding surgical morbidity, no significant difference was noted (CME group: 2 vs. non-CME group: 5; P < 0.702). Conclusion CME appears to be a safe procedure when performed by experienced hands through proper embryological planes. It also provides a superior specimen, with a higher lymph node yield, which consequently affects the lymph node ratio. Eventually, CME with CVL should be increasingly adopted and studied more deeply.